Moving To Become Kromo Lawi - Matanasi, Petrik (JURNAL HISTORICA, 2024)
Mohamad Lawi Soemodihardjo, not as Kromo Lawi. Prior to being known as Kromo Lawi, he was only Mohamad Lawi Soemodihardjo. Lawi Soemodihardjo was born as the son of a manor. Lawi worked for a while at a railway company in Comal, this young man from Batang then enrolled in Koninklijk Marine (KM) or the Royal Dutch Navy. Lawi and his friends later founded the Inlandsch Marine Bond (IMB) on May 25, 1925. Because of his involvement in the PKI rebellion in Banten in 1926, Lawi was fired from the Koninklijk Marine in 1927. Then Lawi returned to Pekalongan and joined the Muhammadiyah. Lawi then joined the PNI led by Sukarno. In 1928 Lawi was entrusted to become a branch of PNI Pekalongan. When PNI dissolved, Lawi later joined in the Partindo led by Mr. Sartono. Lawi became the head of the branch of Pekalongan. In the days of the Sukarno followers, Levi was given the first name Kromo (Kr), so he was known as Kromo Lawi.